ON THE APPLICATION OF MULTISET TO DETERMINISTIC COOPERATIVE SPECIALIZATION P SYSTEM UNDER CATALYSIS (FUDMA JOURNAL OF SCIENCES, 2022)
Quasi-general models of membrane computing have been designed by means of rules which represent the processes taking place in a biological cell without explicitly specifying the specialties of the rules, viz: their mixture, chemical or physical characteristics as is obtainable in a biological cell. In this paper, an attempt to model a variant of membrane computing called specialization P system is made. It is capable of simulating biological activities at cellular level, and as the name implies, in a specialized manner. It is shown that with only one membrane and three rules, a deterministic cooperative specialization P system under catalysis is able to characterize the family of recursively enumerable languages.
Keywords: Multiset, membrane computing, specialization rules, determinism, computational completeness